2020
DOI: 10.1111/jphp.13270
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the biotransformation of N-(2-hydroxyphenyl)-2-propylpentanamide (an aryl valproic acid derivative) by CYP2C11, using in silico predictions and in vitro studies

Abstract: Objectives N‐(2‐hydroxyphenyl)‐2‐propylpentanamide (HO‐AAVPA), a derivative of valproic acid (VPA), has been proposed as a potential anticancer agent due to its improved antiproliferative effects in some cancer cell lines. Although there is evidence that VPA is metabolized by cytochrome P450 2C11 rat isoform, HO‐AAVPA CYP‐mediated metabolism has not yet been fully explored. Therefore, in this work, the biotransformation of HO‐AAVPA by CYP2C11 was investigated. Methods Kinetic parameters and spectral interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
4
0
1
Order By: Relevance
“…Regarding the determination of MDA levels, in the present study it was shown that HO-AAVPA induces a lower degree of lipid peroxidation than the VPA group (Figure 3), suggesting that HO-AAVPA, once metabolized, does not generate reactive intermediates that can lead to the formation of free radicals, but is only capable of producing hydroxylated compounds [18,19]. Regarding the GSH levels in the group treated with HO-AAVPA, these tended to decrease but not like those of the group treated with VPA (Figure 3), which suggests a greater hepatoprotective effect of HO-AAVPA, avoiding severe liver damage after repeated administration [20]. Under the above context, liver injury can be caused by an exogenous or endogenous agent that leads to oxidative stress due to the production of free radicals [34].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the determination of MDA levels, in the present study it was shown that HO-AAVPA induces a lower degree of lipid peroxidation than the VPA group (Figure 3), suggesting that HO-AAVPA, once metabolized, does not generate reactive intermediates that can lead to the formation of free radicals, but is only capable of producing hydroxylated compounds [18,19]. Regarding the GSH levels in the group treated with HO-AAVPA, these tended to decrease but not like those of the group treated with VPA (Figure 3), which suggests a greater hepatoprotective effect of HO-AAVPA, avoiding severe liver damage after repeated administration [20]. Under the above context, liver injury can be caused by an exogenous or endogenous agent that leads to oxidative stress due to the production of free radicals [34].…”
Section: Discussionmentioning
confidence: 97%
“…Part of these effects is attributed to the metabolism of VPA by cytochrome P450 (CYP450), which produces several metabolites, including 4-ene-valproic acid (4-eno-VPA) and 2,4-diene-valproic acid (2,4-diene-VPA) [9], which have been associated with an overproduction of ROS and the consequent loss of cellular homeostasis [16,17]. Regarding HO-AAVPA, it is distributed in various tissues, mainly in the liver, and it suffers biotransformation by the rat liver CYP2C11 isoform, producing hydroxylated metabolites [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…El identificar estos procesos nos puede ayudar a proponer terapias sinérgicas con fármacos ya conocidos con actividad anticáncer. 1,2 La epigenética en medicina es un área que cada día comprende nuevos hallazgos y aplicaciones en diferentes aspectos de la medicina que incluyen el diagnóstico, pronóstico y tratamiento de múltiples enfermedades humanas. Se han propuesto marcadores novedosos para el cáncer humano y de manera específica para el cáncer de mama, lo que ha llamado poderosamente la atención es que los cambios epigenéticos se pueden modificar con cambios de estilo de vida, alimentación, incorporación de alimentos que ayudan a cambiar la metilación de genes, etcétera.…”
Section: Epigenetics and Breast Cancerunclassified
“…Some toxicity studies in a rat model show that HO-AAVPA does not cause liver damage in acute and subchronic treatment, it does not affect organogenesis, and its lethal dose 50 (LD 50 ) 14 is inside the drug toxicity limits recommended 15 . However, during the development and validation of analytical method of HO-AAVPA on reversed-phase high-performance liquid chromatography (RP-HPLC) there was identified a metabolite from a metabolism study into rat liver microsomes 16 which yield two metabolites 17 . In addition, HO-AAVPA has rapid clearance in pharmacokinetic studies in a rat model 18 .…”
Section: Introductionmentioning
confidence: 99%